Sources of borrowing and fiscal multipliers - Romanos Priftis; Srecko Zimic (Bank of Canada, 2018)
This paper finds that debt-financed government spending multipliers vary considerably depending on the location of the debt buyer. In a sample of 33 countries, we find that government spending multipliers are larger when government purchases are financed by issuing debt to foreign investors (non-residents), compared with when government purchases are financed by issuing debt to home investors (residents). A theoretical model (with flexible or sticky prices) shows that the location of the government creditor produces these differential responses to the extent that private investment is crowded out in each case. Increasing international capital mobility of the resident private sector decreases the difference between the two types of financing, both in the model and in the data.
Keywords: E2; E62; F41; H3; 330; Debt management; Economic models; Fiscal policy; International financial markets